2013
DOI: 10.1016/j.jviromet.2012.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Immunoreactivity characterisation of the three structural regions of the human coronavirus OC43 nucleocapsid protein by Western blot: Implications for the diagnosis of coronavirus infection

Abstract: Previous studies have reported that a prokaryotic-expressed recombinant nucleocapsid protein (NP) is a suitable reagent for the epidemiological screening of coronavirus infection. In this study, soluble recombinant human coronavirus OC43 (HCoV-OC43) NP was produced to examine the antigenicity of the HCoV-OC43 NP of betacoronavirus. Using the purified recombinant NP as an antigen, a polyclonal antibody from rabbit serum with specificity for HCoV-OC43 NP was generated; this antibody reacts specifically with HCoV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 45 publications
0
33
0
Order By: Relevance
“…While exact dynamics from 6 months to 20 years vary between studies, the general trend remains consistent. Figure 7 displays HCoV ageseroprevalence curves for the 7 papers with digitizable data on seroprevalence by age, with the panels representing the four major endemic strains 74,[110][111][112][113][114][115] . Trends from papers not displayed in the figure are largely the same 68,70,116,117 .…”
Section: Seroprevalence To Endemic Coronaviruses Increases Rapidly Dumentioning
confidence: 99%
See 1 more Smart Citation
“…While exact dynamics from 6 months to 20 years vary between studies, the general trend remains consistent. Figure 7 displays HCoV ageseroprevalence curves for the 7 papers with digitizable data on seroprevalence by age, with the panels representing the four major endemic strains 74,[110][111][112][113][114][115] . Trends from papers not displayed in the figure are largely the same 68,70,116,117 .…”
Section: Seroprevalence To Endemic Coronaviruses Increases Rapidly Dumentioning
confidence: 99%
“…The review gave rise to several observations that were either consistent or conflicting across papers. Studies that enrolled children less than 6 months detected loss of maternal antibodies, representing a preliminary line of defense for newborn children 70,71,74,117 . Most studies showed no discernible difference in age-seroprevalence trends or in overall seroprevalence by strain.…”
Section: Further Observations From Reviewmentioning
confidence: 99%
“…Studies reported that the N protein produced from prokaryotes has been used to generate specific antibodies against various animal coronaviruses including SARS (Loa et al, 2004;Timani et al, 2004;Wu et al, 2004aWu et al, , 2004bBlanchard et al, 2011). The recombinant antigenic N protein from hCoV OC43 used against the rabbit polyclonal antibodies specific for hCoV OC43 and did not crossreact with other coronaviruses (SARS CoV and hCoV 229E) (Liang et al, 2013). Moreover, it was tested in different aged human serum samples and exhibited strong reactivity due to the effective central portion (174-300 amino acids) of the N protein followed by C (301-448) & N (1-173) terminal portions Yu et al, 2008;Liang et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The recombinant antigenic N protein from hCoV OC43 used against the rabbit polyclonal antibodies specific for hCoV OC43 and did not crossreact with other coronaviruses (SARS CoV and hCoV 229E) (Liang et al, 2013). Moreover, it was tested in different aged human serum samples and exhibited strong reactivity due to the effective central portion (174-300 amino acids) of the N protein followed by C (301-448) & N (1-173) terminal portions Yu et al, 2008;Liang et al, 2013). Hence the N protein functions as a sensitive and specific diagnostic tool for hCoV OC43 (Di et al, 2005;He et al, 2005) and it has been further useful in the detection of SARS CoV infection (after the first day of infection) (Che et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown to act as an RNA chaperone [21]. Moreover, the N protein is an important diagnostic marker and is an antigen for the host antibody and T cell immune responses [16,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%